EFFECT OF MARKETING ETHICS AS A MODERATE ON THE RELATIONSHIP BETWEEN MARKET ORIENTATION AND SME PERFORMANCE: EVIDENCE FROM SAUDI ARABIA - Moad Hamod M Saleh; Adi Anuar Azmin; Ummi Naiemah Saraih (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Literature has revealed, recently, the importance of market orientation (MO) for firm performance (SMEs); However, doubts still about how MO could improve SMEs performance exist due to the vagueness surrounding it. We examine marketing ethics (ME) that moderate the MO-SMEs relationship. A proposed model was analyzed empirically using a structural equation model (SEM) drawing on survey data for 408 manufacturing SMEs in Saudi Arabia. The results obtained show that MO positively affects performance for SMEs and, most significantly, this relationship is indirect as it is fully moderated by ME. These findings reveal MO improves performance when those firms make efforts in developing marketing ethics. the market orientation is significant, but it may not be sufficient to improve performance if the firm is unable to follow the marketing ethics practices.